2021
DOI: 10.1186/s40545-021-00383-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-directed vancomycin therapeutic drug monitoring in pediatric patients: a collaborative-practice model

Abstract: Background Therapeutic drug monitoring (TDM) of Vancomycin (VCM) is required to prevent inappropriate dosage-associated bacterial resistance, therapeutic failure, and toxicities in pediatrics. Anecdotal experience and studies show that many healthcare institutions confront barriers while implementing TDM services, this study aimed to assess a pharmacist-directed VCM–TDM service for optimizing patient care in our institution. Materials and methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…For instance, the expansion of pharmacists’ role in an orthopedic unit in Australia ensured correct weight-based dosing and SAP duration [ 22 ]. In another recent quasi-experimental study, pharmacists had a pivotal role in optimizing the initial vancomycin doses and dose adjustments [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the expansion of pharmacists’ role in an orthopedic unit in Australia ensured correct weight-based dosing and SAP duration [ 22 ]. In another recent quasi-experimental study, pharmacists had a pivotal role in optimizing the initial vancomycin doses and dose adjustments [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Recently, it has been observed that this profession is gradually growing in Pakistan in private set-up. [19][20][21] However despite this improvement, the precise role of pharmacist as healthcare profession in Pakistan is still challenging. Within the sphere of pediatric cardiac setting, a notable scarcity of substantial data prevails in Pakistan, illuminating the comprehensive elucidation of the pivotal role and engagement of pharmacist in clinical activities.…”
Section: Pharmacist Clinical Access Constraints In Pakistanmentioning
confidence: 99%
“…Evidence also suggests the integration of pharmacy services in TDM can impact positively on patient care, with improved sampling time and clinical interpretation of drug levels leading to more efficient and cost-effective delivery of care [ 12 , 13 ]. There is evidence to suggest that, when pharmacists are directly involved in ordering pathology and dose adjustments, substantial cost savings can be demonstrated by reducing inappropriate requests and increasing the optimization of initial dosing for medications such as antibiotics [ 12 , 13 , 14 , 15 ]. Although evidence has demonstrated the benefits of these TDM services, the extent to which healthcare settings in Australia have made use of the knowledge and skills of pharmacists to provide high-level, patient-focused services within this area is not known [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%